Effect Of Price, Perceived Easy Of Use, E-Wom On Purchase Decision Of Tiktok Shop In Medan - Selli Selfia; Hafiza Adlina (Cattleya Darmaya Fortuna, 2022)
Tiktok Shop which is a new feature of Tiktok, has very large sales, the popularity of Tiktok at this time has spread in various countries in the world. this study aims to analyze the influence of price, perceived ease of Use, and e-wom on purchasing decisions on the Tiktok Shop application. the research method used is quantitative with an associative approach. The results showed that the price and perception of ease of use significantly affect the purchase decision. Meanwhile E-WOM has no significant effect against the purchase decision. But the price, the perception of ease of use, and e-WOM influence together (simultaneously) to the purchase decision.